2018
DOI: 10.21873/cgp.20090
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Plasma miR-21-5p Is a Sensitive Biomarker and Independent Prognostic Factor in Patients with Pancreatic Ductal Adenocarcinoma Undergoing Surgical Resection

Abstract: Blood plasma microRNAs (miRNAs) are emerging as a clinically useful tool for non-invasive detection and prognosis estimation in various cancer types including pancreatic ductal adenocarcinoma (PDAC). The aim of the present study was to provide an independent validation of circulating miRNAs identified in previous studies as diagnostic and/or prognostic biomarkers in PDAC. Based on the literature search, 6 miRNAs were chosen as candidates for independent validation; miR-21-5p, miR-375, miR-155, miR-17-5p, miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…In addition, a high exosomal miR-21 expression was associated with poor OS in pancreatic cancer patients (median OS of 344 vs. 846 days for low expression) (78). These results are consistent with Karasek et al results which concluded that plasma levels of miR-21 were significantly higher in PDAC compared to healthy controls and associated with poor OS in PDAC (79).…”
Section: Kras Mutation In Circulating Evs As a Biomarker Of Pdacsupporting
confidence: 92%
“…In addition, a high exosomal miR-21 expression was associated with poor OS in pancreatic cancer patients (median OS of 344 vs. 846 days for low expression) (78). These results are consistent with Karasek et al results which concluded that plasma levels of miR-21 were significantly higher in PDAC compared to healthy controls and associated with poor OS in PDAC (79).…”
Section: Kras Mutation In Circulating Evs As a Biomarker Of Pdacsupporting
confidence: 92%
“…Besides the tested EMT-regulating microRNAs, other microRNAs have been connected with great potential as biomarkers in PDAC as well. Among others, microRNAs -21, -155, -196a and -210 are shown to be potential non-invasive biomarkers for diagnosis, prognosis and/or therapy response [ 19 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Moreover, microRNA-21 antisense oligonucleotides are also linked with high potential in PDAC therapy as a partner for gemcitabine [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PDAC, both overexpression and downregulation of specific miRNAs have been associated with poor prognosis. Among others, higher levels of circulating miR-21, miR-155 and miR-221 correlated with outcomes [46][47][48][49]. Interestingly, the miRNA 200s family has been shown to suppressor tumor progression via EMT inhibition [50].…”
Section: Microrna and Long Non-coding Rnamentioning
confidence: 99%